Farmers’ Perceptions of Community Outreach Activities in Mukono District Uganda - Rostand Biluge Kaboyi (Uganda Christian University, 2025)
Agricultural outreach activities serve as vital channels through which universities disseminate knowledge to local farmers in surrounding communities. This study evaluated farmers' perceptions regarding the effectiveness of Uganda Christian University's (UCU) agricultural outreach programs in Mukono District, employing a mixed-methods approach with surveys from 60 farmers and interviews with 3community leaders across different villages. The study revealed that most farmers (91.6%) perceived the program as effective in influencing their agricultural practices. Crop-related activities received the highest appreciation (74.7%), particularly vegetable farming (81.3%) and garden farming(76.2%). While 70% of farmers reported improved agricultural productivity from program participation, only 55% experienced corresponding increases in household income, indicating a gap between productivity gains and economic benefits. Furthermore, just 36.7% of farmers acknowledged program contributions to climate change adaptation. Farmers faced five main categories of challenges: resource constraints (30%), knowledge and literacy limitations (30%), environmental factors (20%), follow-up and continuity issues (10%), and market access problems (10%). Despite these challenges, all participants (100%) expressed willingness to accommodate more students, reflecting the perceived value of knowledge exchange. The study concludes that UCU's outreach program significantly influences agricultural knowledge implementation in Mukono District, particularly in crop production. However, to enhance program effectiveness, UCU should incorporate climate-smart agriculture practices, strengthen market linkages, develop diverse teaching methodologies accommodating various educational backgrounds, introduce compact agricultural technologies for limited land, establish systematic follow-up mechanisms, and build strategic partnerships with market actors to help farmers translate productivity improvements into tangible economic benefits.
Undergraduate